Design of IoT Gateway for Crop Growth Environmental Monitoring Based on Edge-Computing Technology. (14th July 2022) - Dong, Mo; Yu, Haiye; Sun, Zhipeng; Wu, Mingzhi; Zhang, Lei; Sui, Yuanyuan; Yu, Guanghao; Han, Ting; Zhao, Ruohan
Abstract : With the extensive use of the Internet of Things (IoT) in agriculture, the number of terminals are also grow rapidly. This will increase the network traffic and computing pressure of the centralized server. The centralized data processing mode used in traditional agriculture cannot meet the needs of the Internet of everything era. This paper designs a gateway based on edge-computing technology for monitoring crop growth environment. It uses virtualized container technology to package long-range wide-area network (LoRaWAN) server, pest identification, and environmental information data fusion functions into images. It forms integrated operation mode of multiple function in agriculture. The gateway applies message-oriented middleware to standardize and customize the data transmission among functional modules, clouds, and edges. Through simulation and field test, the designed gateway can achieve the functions of each module at the same time, the resource utilization, and the transmission quality are stable. The edge-computing gateway has the advantages of low cost, low latency, and low power consumption which has practical significance.